ANALYSIS OF THE VALIDITY OF LANGUAGE USE IN THE EXAMINATION MINUTES (BAP) OF SUSPECTS AT THE GOWA POLICE CRIMINAL INVESTIGATION UNIT (FORENSIC LINGUISTIC STUDY) - Sartika, Dewi; Sukri Syamsuri, Andi; Paida, Andi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the validity of the use of language in the Investigation Report (BAP) of the Suspect in the Gowa Police Criminal Investigation Unit through a forensic linguistic study. The focus of the research is directed at four linguistic aspects, namely diction, syntax, coherence, and ambiguity, which have the potential to affect the accuracy, clarity, and consistency of information in BAP documents. This study uses a qualitative approach with a case study design, involving five Suspect BAP documents as primary data analyzed through qualitative content analysis techniques using the interactive model Miles, Huberman, and Saldaña. The results of the study show that the use of diction in some BAPs does not fully reflect the suspect's literal statements, but is a narrative construction of the investigator that has the potential to cause meaning bias. In the syntax aspect, it was found that the sentence structure was long, ineffective, and layered so that it gave rise to the blurring of the subject of action and the flow of information. The aspect of coherence also shows irregularities in the organization of the chronology which results in the flow of events becoming illogical and making it difficult to understand the sequence of events. Meanwhile, referential and semantic ambiguity is found in a number of parts of the BAP, especially related to the use of unclear pronouns that open up the possibility of double interpretation. These findings indicate that the linguistic aspect plays a crucial role in the validity of BAP as a legal document. Linguistic inaccuracy has the potential to affect the interpretation of law enforcement officials and have an impact on the fulfillment of suspects' rights. This study emphasizes the need to improve language competence for investigators and the application of forensic linguistic principles in the preparation of investigation documents.